Nematicide evaluation of the essential oil from Tagetes zypaquirensis in the control of the nematode Meloidogyne spp. - Álvarez S., David Eduardo; Botina J., Jennifer Aleida; Ortiz C., Abner Jarminton; Botina J., Lorena Lisbetd (Revista de Ciencias Agrícolas, 2016)
Lulo (Solanum quitoense Lam.), an Andean fruit, is economically important in Colombia, however, cultivated areas as well as yields, have suffered a considerable reduction by the attack of pathogens such as the rootknot nematode Meloidogyne spp. with losses near to 50%. In nature, there are different plant with nematicides properties which could diminish the effects of this nematode, such as the Tagetes genre. The objective of this research was to evaluate the nematicidal activity of the essential oil from Tagetes szypaquirensis on Meloidogyne spp. Four concentrations of essential (100, 200, 400, 800mg/kg of soil) were evaluated under greenhouse conditions. These doses were applied to nematodes in the second instar approximately +400 J2/100g of soil. Moreover, three treatments were established: the first with no application of essential oil, the second without nematode, and the third with soil treated with carbofuran (33.2%) at dose of 2cc/L. For each treatment the variables evaluated were: level of severity, plant height, fresh and dry weight, fresh root weight, number of nematode eggs/100g roots and number of J2/100g of soil. The main components of the essential oil from T. zypaquirensis were dihydrotagetone and E-tagetone with a composition of 42.2% and 22.9% respectively. The results indicated that a concentration 800mg/kg of essential oil had the same nematicidal action than soil treated with carbofuran, same population constrains and phitometric variables. It was concluded that T. zypaquirensis essential oil can be an alternative for managing root knot disease.